Review of Intra-Articular Use of Antibiotics and Antiseptic Irrigation and Their Systematic Association with Chondrolysis - Post, Hunter; Blankespoor, Michael; Ierulli, Victoria; Morey, Tucker; Schroeppel, J. Paul; Mulcahey, Mary; Vopat, Bryan; Vopat, Matthew (Kansas Journal of Medicine, 2023)
Introduction. Intra-articular antibiotics have been proposed as a treatment for septic arthritis to allow for high local concentrations without subjecting a patient to the toxicity/side effects of systemic therapy. However, there is concern for chondrotoxicity with intra-articular use of these solutions in high concentrations. The purpose of this systematic review was to evaluate the intra-articular use of antibiotics and antiseptic solutions, and to determine their association with chondrolysis following in vitro or in vivo administration.Methods. A systematic review was conducted following PRISMA guidelines through PubMed, Clinical Key, OVID, and Google Scholar. Studies in English were included if they evaluated for chondrotoxicity following antibiotic exposure.Results. The initial search resulted in 228 studies, with 36 meeting criteria. Overall, 7 of the 24 (29%) agents were non-chondrotoxic: minocycline, tetracycline, chloramphenicol, teicoplanin, pefloxacin, linezolid, polymyxin-bacitracin. Eight (33%) agents had inconsistent results: doxycycline, ceftriaxone, gentamicin, vancomycin, ciprofloxacin, ofloxacin, chlorhexidine, and povidone iodine. Chondrotoxicity was evident with 9 (38%) agents, all of which were also dose-dependently chondrotoxic based on reported estimated half maximal inhibitory concentrations (est.IC50): amikacin (est. IC50 = 0.31-2.74 mg/mL), neomycin (0.82), cefazolin (1.67-3.95), ceftazidime (3.16-3.59), ampicillin-sulbactam (8.64 - >25), penicillin (11.61), amoxicillin (14.01), imipenem (>25), and tobramycin (>25). Additionally, chondroprotective effects of doxycycline and minocycline were reported.Conclusions. This systematic review identified agents that may be used in the treatment of septic arthritis. Nine agents should be avoided due to their dose-dependent chondrotoxic effects. Further studies are needed to clarify the safety of these medications for human intra-articular use.